Study of the effect of sodium sulphate on shear strength properties of bentonite clay - Nazem, Samira (Curtin University, 2015)
This study examined the influence of Sodium Sulphate on the shear strength characteristics of bentonite. A series of direct shear tests were carried out on the specimens prepared with various contents of salt and different curing times to up to 365 days. The results were used to predict the behaviour of pure bentonite and the bentonite mixed with sulphate in two typical geotechnical problems by the use of finite element software, Plaxis code.